Differences in Anxiety Levels of Menopausal Women Before and After Given Psychoeducation and Relaxation - Fitra Ermila Basri; Yuliarni Syafrita; Yantri Maputra (Institute of Computer Science (IOCS), 2021)
Menopause is a transitional period in a woman's life that shows that the ovaries have stopped producing eggs, menstrual activity decreases and finally stops.. One of the treatments for this complaint is non-pharmacological therapy, namely psychoeducation and relaxation. The research objective was to determine the differences in the anxiety levels of menopausal women before and after psychoeducation and relaxation. This research is a quasy experiment with one group pretest and posttest design. The research was conducted at the Elderly Posyandu in the working area of ​​the Dadok Tunggul Hitam Community Health Center to 54 menopausal women who were divided into a treatment group and a control group. The results showed that most respondents in the treatment and control groups prior to psychoeducation and relaxation were in the mild anxiety level category. After doing psychoeducation and relaxation, there was a decrease in anxiety levels in the treatment group.Based on the t test, the p-value is less than 0.05, it can be concluded that there are differences in the level of anxiety in menopausal women before and after psychoeducation and relaxation. (p =0.001). The conclusion of this study is that there are differences in the decrease in anxiety levels after psychoeducation and relaxation.